2016
DOI: 10.24275/rmiq/alim1044
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of Solutions of Gelatin Withbentonite and Tannic Acid

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…35 The G-nTA solution presented the lowest viscosity, most likely due to the plasticizing effect of tannic acid (TA) at high concentrations. 36 The highest viscosity was found for G-nTA-CNC6, which increased by a factor of 180 and 6 compared to G-nTA and G-OTA-CNC6, respectively. Sun et al 37 observed similar behavior for gelatin-encapsulated tea polyphenol dispersions with CNC, which exhibited a positive effect on viscosity, increasing from 67 to 122 mPa s. For all solutions, the R 2 of shear-thinning curves was higher than 0.90, confirming that the power law model was suitable to describe the rheological behavior of the gelatin-based solutions prepared here.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…35 The G-nTA solution presented the lowest viscosity, most likely due to the plasticizing effect of tannic acid (TA) at high concentrations. 36 The highest viscosity was found for G-nTA-CNC6, which increased by a factor of 180 and 6 compared to G-nTA and G-OTA-CNC6, respectively. Sun et al 37 observed similar behavior for gelatin-encapsulated tea polyphenol dispersions with CNC, which exhibited a positive effect on viscosity, increasing from 67 to 122 mPa s. For all solutions, the R 2 of shear-thinning curves was higher than 0.90, confirming that the power law model was suitable to describe the rheological behavior of the gelatin-based solutions prepared here.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…The G-nTA solution presented the lowest viscosity, most likely due to the plasticizing effect of tannic acid (TA) at high concentrations . The highest viscosity was found for G-nTA-CNC6, which increased by a factor of 180 and 6 compared to G-nTA and G-OTA-CNC6, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With a high gelatin concentration, gelatin molecules decreased the Mt particle size. A stiff network among Mt layers, gelatin, and water molecules was created, which had a strong resistance to flow under shear force, 55 leading to a significant improvement in the rheological properties.…”
Section: Rheological Analysismentioning
confidence: 99%
“…In addition, the characterization of time-dependent rheological properties of food systems is important to establish relationships between structure and flow(Table 2). 23,24…”
Section: Enhancement the Antibacterial Agent Of Edible Coating And Fi...mentioning
confidence: 99%
“…But if its Zeta potential lies between +30 to -30mV, they tend to attract each other and to flocculate. 24,25 Zeta potential: It is clear from the results of the study that zeta potential and zeta deviation was measured to determine the stability of nanoparticle, it depends on the of nanoparticle size of samples (a , b , c , d and e) of edible films nanomaterial's, solution as shown in Table 3 and Figure 4. The results of zeta potential (mv) and zeta deviation were as follows: (13.4,14.5,17.7,15.7and 20.2) respectively and zeta deviation: (2.97,3.30,4.06,2.68,and 4.02 ) respectively, whereas found that the Figure 6 characterization of the one peak of zeta potential and zeta deviation the area below the curve was 100% found that the contents of zeta potential in transactions on peak ( f , g , h , i and j) had zeta potential (mV) ( 5.58,5.13,6.03,5.65 and 5.48 ) respectively , as well as the contents of zeta deviation in transactions on peak ( 2.68,2.67,3.46,3.35 and 3.11 ) respectively.…”
Section: Nanotechnology Measurements In Solutions In the Specified Pr...mentioning
confidence: 99%